Romanticism and the rise of history - Bann, Stephen (New York Twayne Publishers Toronto Maxwell Macmillan Canada ;|aNew York Maxwell Macmillan International, 1995)
Romanticism and the Rise of History, Bann argues that history came of age in Europe during the period following the French Revolution through the end of the nineteenth century, becoming an object of widespread desire. As one perhaps mildly astonished scholar noted later, it was a time when "the most simple-minded farmhand" was "able to distinguish an old belfry from a new one," and, Bann might add, perceive value in the old one.
1. Romanticism and the Desire for History -- 2. Understanding the Past -- 3. Historians on History and Fiction -- 4. The Contemporary Analysis of History and Its Antecedents -- 5. Metamorphoses of Joan of Arc -- 6. The Splitting of Historical Consciousness -- 7. Taking a Subjective Stance -- 8. Staging the Past -- 9. Living the Past.
Includes bibliographical references (p. 179-183) and index.
Donated by Frank Villanueva
Keywords: History -- Philosophy; Romanticism